Distributed query processing for structured and bibliographic databases - LIM, Ee Peng (Institutional Knowledge at Singapore Management University, 1997)
To support future digital library systems which draw information from different sources on the internet, we have to provide integrated queries to pre-existing database servers which contain structured, semi-structured and unstructured data. In this paper, we specifically examine the problem of querying both existing structured relational databases and bibliographic databases. By adopting the well-accepted Z39.50 standard protocol to access bibliographic databases in different legacy library systems, we have developed an extended SQL model, known as HarpSQL, to support integrated queries to both SQL databases and bibliographic databases. Using HarpSQL, one can not only query bibliographic databases in an SQL manner, but also perform join(s) between SQL and bibliographic databases. A distributed query processor supporting HarpSQL queries has been developed. We will present our query processing strategy that is based on client-server interaction model between the distributed query processor and the various remote database servers.